2019
DOI: 10.1371/journal.pone.0216073
|View full text |Cite
|
Sign up to set email alerts
|

Circadian onset and prognosis of myocardial infarction with non-obstructive coronary arteries (MINOCA)

Abstract: Background Many acute cardiovascular events such as myocardial infarction (MI) follow circadian rhythms. Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a newly noticed entity with limited data on onset pattern and its impact on prognosis. Material and methods In this observational study of Swedish MINOCA patients registered in the SWEDEHEART registry between 2003–2013 and followed until December 2013 we identified 9,092 unique patients with MIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
3
13
0
1
Order By: Relevance
“…Although MINOCA was less often diagnosed in NWD, it was not associated with higher long-term mortality. As has been shown in the SWEDEHEART registry, MINOCA occurred most frequently in the morning (incidence rate ratio [IRR] 1.70, 95% CI 1.63-1.84) and on Mondays (IRR 1.28, 95% CI 1.18-1.38) and also less often at the weekends [38]. Comparably to our study, the time of MINOCA occurrence did not affect the long-term prognosis [38].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although MINOCA was less often diagnosed in NWD, it was not associated with higher long-term mortality. As has been shown in the SWEDEHEART registry, MINOCA occurred most frequently in the morning (incidence rate ratio [IRR] 1.70, 95% CI 1.63-1.84) and on Mondays (IRR 1.28, 95% CI 1.18-1.38) and also less often at the weekends [38]. Comparably to our study, the time of MINOCA occurrence did not affect the long-term prognosis [38].…”
Section: Discussionsupporting
confidence: 84%
“…As has been shown in the SWEDEHEART registry, MINOCA occurred most frequently in the morning (incidence rate ratio [IRR] 1.70, 95% CI 1.63-1.84) and on Mondays (IRR 1.28, 95% CI 1.18-1.38) and also less often at the weekends [38]. Comparably to our study, the time of MINOCA occurrence did not affect the long-term prognosis [38]. That circadian onset is probably associated with the pathophysiology of MINOCA [39].…”
Section: Discussionmentioning
confidence: 68%
“…Some have considered binge alcohol consumption on weekends as a reason for increased cardiovascular deaths [26]. Others have found lower incidences of myocardial infarction with non-obstructive coronary arteries (MINOCA) on Saturdays and Sundays [27]. Kostis et al found no differences in the demographic characteristics of the population suffering from acute myocardial infarction between weekdays and weekends [28].…”
Section: Limitationsmentioning
confidence: 99%
“…The seasonal variation of MINOCA and MI-CAD is different, and the incidence of MINOCA increases slightly in summer and autumn. MINOCA and MI-CAD are most common in the morning [18], and some studies have found that the onset time of MINOCA is not correlated with the prognosis of the disease [19].…”
Section: Prevalence Clinical Features and Epidemiologymentioning
confidence: 99%